How Much Have We Changed? Long-Term Determinants of Attitudes toward Homosexuality in Chile. - Paradela-López, Miguel; Antón, José-Ignacio; Jima-González, Alexandra (Latin American Research Review, 2023)
This study explores the evolution of individual attitudes toward homosexuality in Chile during the period 1998–2018. Based on microdata from the International Social Survey Programme, it finds evidence of a significant rise in the share of people accepting homosexual relationships, from 5.4 percent to 38.5 percent of the population. Observable individual-level socioeconomic characteristics are responsible for only 3.6 percentage points of this shift. In particular, the increase in educational attainment and generational replacement help to explain this trend and account for an increase of 2.6 percentage points (roughly 45 percent of the initial level of acceptance). Nevertheless, the bulk of this shift is due to structural changes in Chilean society, which may have increased acceptance across all the demographic subgroups considered in the analysis.